The length of the biliopancreatic limb in one anastomosis gastric bypass - Focquet, Marc (Frontiers in Surgery, 2024)
Obesity has become a real global pandemic responsible for severe associated diseases as there are diabetes type 2, hypertension, sleep apnea, arthritis, hyperlipidemie and others so its treatment is of paramount importance. Among the different treatments (diets, medication, physical activity, counseling, psychotherapy ), weight loss surgery is probably the most effective therapy at this moment. The potential mechanisms and physiology of weight loss surgery are multifactorial and not fully elucidated : age, genetics, changes in gut microbiota, alterations in bile, gut hormones ( GLP1 , PYY) , food restriction and hypo-absorption are some of the key-factors.Today dysfunctional neuroendocrine signals are held responsible for an impaired ingestion resulting in overweight and obesity so bariatric surgery has become bariatric-metabolic surgery if not purely "metabolic surgery" (1).The one-anastomosis gastric bypass (OAGB) , first published by Dr Rutledge in 1997 is now a wellestablished procedure in the bariatric-metabolic armamentarium .This procedure based on a ( single) loop gastro-jejunal anastomosis ( the biliopancreatic limb or BPL ) with a long narrow gastric pouch combines restriction with hypo-absorption. The biliopancreatic limb and in particular its length is held responsible for the degree of the hypo-absorptive effect but the most appropriate or " optimal " length of the BPL remains debatable .The following text intends to summarize the different options in search of the ideal limb lengths not only to optimize the outcomes of the OAGB in terms of weight loss and resolution of obesityassociated diseases but also to reduce potential side-effects in particular nutritional deficiencies. Fig 1 : one anastomosis gastric bypass: long gastric pouch (yellow), biliopancreatic limb (green)Limitations : the following text is not a systematic review but the result of a comprehensive and meticulous selection of the most recent literature in Cochrane, Pubmed and Google Scholar based on the search term "biliopancreatic limb" and more specific "the biliopancreatic limb in one anastomosis gastric bypass".